Weather Condition, Seasonal Variation and Ball Development Pattern in Relation to Rice False Smut Disease in Bangladesh - Nessa, B; Salam, MU; Haque, AHMM; Kashem, MA; Kabir, MS (Bangladesh Rice Journal, 2019)
Rice false smut (RFSm) is an international disease. The effect of the disease has become seriously evident in Bangladesh since 2010. The disease is predominant in the country in the ‘T. Aman’ rice growing season. Its occurrence in other rice growing seasons not well studied and recorded. Information on driving weather variable(s) causing the disease epidemic is scanty and not ground-truthed. This study, conducted in the experimental farm of the Bangladesh Rice Research Institute, Gazipur, Bangladesh, attempted to fill those information gaps. The association of disease incidence and weather parameters such as relative humidity, cloud hour and rainfall, was inconsistence except for the daily average temperature. High disease incidence occurred when the average temperature during panicle emergence period ranged between 22-27°C; any temperature below or above the range linearly decreased the disease incidence. RFSm disease was recorded in the study area in all the months, except for in February and March. The distribution in the incidence of disease in the three rice growing seasons followed the order of ‘T. Aman’ > ‘Aus’ > ‘Boro’; it was ~ six times less in ‘Aus’ and ~ eight times less in ‘Boro’ season, compared to ‘T. Aman’ season. New balls formed on infected panicles in batch by batch. High number of such batches formed in ‘T. Aman’ season. The final status of the disease in an infected crop was the accumulation of incidence of the disease in each batch. This study provided key epidemiology on the development of RFSm in nature and it is concluded such information on the disease under local conditions would be the key to designing management options. Bangladesh Rice j. 2018, 22(1): 57-64